Analisis Strategi Inovasi Produk Nasgortri untuk Menarik Minat Beli Pelanggan di Bengkayang - Elisabet Elisabet; Benedhikta Kikky Vuspitasari; Sabinus Beni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Culinary in Indonesia today has a variety of characteristics that continue to develop in accordance with the ideas and thoughts embraced by business actors. Business actors must be able to see and take advantage of the potential business opportunities in the surrounding environment so that they can become a source of income in their business activities. In the fried rice business run by Nasgortri, it is inseparable from the innovations and marketing strategies applied to it, there are qualified innovations such as modulation approaches, complementary ingredient approaches and business reduction approaches, which are service standards that must be complied with. This study uses a qualitative approach with a descriptive method. The data collection technique consists of observation and interviews. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of data analysis show that NASGORTRI's fried rice business in running the business offered to consumers applies several sales strategies using methods of approach, including modulation approaches, complementary ingredients, and effort reduction.